Evaluation of the Effects of Peritoneal Lavage with Rosmarinus officinalis Extract against the Prevention of Postsurgical-Induced Peritoneal Adhesion - Roohbakhsh, Yasamin; Baradaran Rahimi, Vafa; Silakhori, Samaneh; Rajabi, Hamed; Rahmanian-Devin, Pouria; Samzadeh-Kermani, Alireza; Rakhshandeh, Hassan; Hasanpour, Maede; Iranshahi, Mehrdad; Mousavi, Seyed Hadi; Askari, Vahid Reza (Planta Medica, 2020)
Postoperative adhesions are regarded as the major complication following abdominal surgery. Rosmarinus officinalis has shown antioxidative and anti-inflammatory effects. Therefore, we aimed to assess the influence of 70% v/v hydro-ethanolic extract of the aerial parts of R. officinalis against postoperative abdominal adhesions in a rat model. Forty-eight male Wistar rats (190 ± 20 g) were divided into six groups of eight: group 1 = normal group, without any surgical procedures, group 2 = control group, group 3 = vehicle group, and groups 3, 4, and 5 = experimental groups receiving 2 mL of 4, 2, or 1% w/v R. officinalis treatment. Adhesion levels were macroscopically examined. Additionally, the levels of inflammatory cytokines (interleukin-6, interleukin-1β, and TNF-α), growth factors (transforming growth factor-β1, and vascular endothelial growth factor), oxidative (NO, nitric oxide and MDA, malondialdehyde), and antioxidative (GSH, glutathione) factors were evaluated. Our results revealed that the adhesion score, interleukin-6, interleukin-1β, TNF-α, transforming growth factor-β1, vascular endothelial growth factor, NO, and MDA levels were significantly increased in the vehicle group, while the GSH level was diminished. R. officinalis treatment notably ameliorated the adhesion score following postoperative abdominal adhesions compared with the vehicle group. Our results also revealed that R. officinalis markedly reduced inflammatory cytokines, oxidative factors, fibrosis, and angiogenesis biomarkers, whereas it increased the antioxidative factor. Therefore, R. officinalis may be a potential candidate for the management of postoperative peritoneal adhesion.
Keywords: Rosmarinus officinalis; peritoneal adhesion; inflammation; antioxidant activity; TGF-β; Lamiaceae